2018
DOI: 10.4236/as.2018.98065
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Relationship between Testicular Echotexture and Seminal Characteristics in Adult Texel Rams

Abstract: The objective of this study was to determine the minimum representative area to evaluate testicular echotexture parenchyma and to identify the correlations between the intensity of pixels of the testicular parenchyma and the fibrosis score with the physical and morphological characteristics of the ejaculate of Texel rams. The study used 88 Texel rams, aged between 10 and 12 months, and reared in a semi-extensive system. The animals underwent breeding soundness evaluation (BSE) and ultrasound of the testicles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A testicular echogenicity varying highly with age, associated with an initial increase followed by a decline, corresponding to the mitotic and postmitotic phases of spermatogenesis in prepubescent ram lambs was reported by Giffin et al (2014). Urt et al (2018) related the differences in testicular parenchymal echogenicity to the stage of sexual maturity of the rams studied (end of puberty and beginning of sexual maturity) and the anatomical changes of the seminiferous tubules. Camela et al (2019) accepted that the difference in testicular echotexture was due to changes of the testes' histomorphology occurring at puberty and explaining the decline in both echotextural variables with seminiferous tubule area differentiation, manifesting in the presence of more mature germ cells in the majority of seminiferous tubules.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 70%
See 3 more Smart Citations
“…A testicular echogenicity varying highly with age, associated with an initial increase followed by a decline, corresponding to the mitotic and postmitotic phases of spermatogenesis in prepubescent ram lambs was reported by Giffin et al (2014). Urt et al (2018) related the differences in testicular parenchymal echogenicity to the stage of sexual maturity of the rams studied (end of puberty and beginning of sexual maturity) and the anatomical changes of the seminiferous tubules. Camela et al (2019) accepted that the difference in testicular echotexture was due to changes of the testes' histomorphology occurring at puberty and explaining the decline in both echotextural variables with seminiferous tubule area differentiation, manifesting in the presence of more mature germ cells in the majority of seminiferous tubules.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 70%
“…Regarding the intensity of the pixels of the predetermined regions and the testes position, Urt et al (2018) observed a difference between left and right testes when testicular parenchyma with area of 400 mm 2 was examined. Because of that, they recommended average intensity of the pixels of the left and right testes of the 1600 mm 2 area (40 x 40 mm) for correct echotexture analysis.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 97%
See 2 more Smart Citations
“…These range from 0 (absolute black) to 255 (absolute white) and provide an indication of tissue echogenicity [ 14 ]. Thereby, ultrasound analysis has been used to predict the reproductive soundness of rams [ 15 , 16 , 17 ] or the detection of pubertal changes in lambs [ 18 , 19 ]. However, in these previous studies, the ultrasound images were evaluated by non-specific image-analysis software (such as Image ProPlus ® or Image J), which could decrease the sensitivity and reproducibility of the results.…”
Section: Introductionmentioning
confidence: 99%